Peranan Etika Kristen Dalam Membangun Pranikah Yang Kudus Bagi Remaja Kristen - Zuniasa Nazara (Ra'ah: Journal of Sociology of Religion, 2021)
Ethics are matters relating to the principles, morals, decency, inner feelings and tendencies of the human heart that are formed in the human environment itself. Christian ethics is based more on the teachings of the Lord Jesus Christ who is an example and role model in life. Christian ethics is a response to divine grace. Christian ethics does not only talk about spiritual and church matters but also worldly matters. The sources of Christian Ethics are the Bible, God. Jesus Christ. The purpose of Christian ethics is to determine what is appropriate and inappropriate for Christians to do both in relationships, dating and determining the direction of life. Christian ethics plays a role in how Christian youth build a holy premarital and the role of parents and the church in building the lives of teenagers when building a premarital relationship or establishing relationships between them.